Experimental investigation on the effect of ligands on copper(I)oxide/copper(II)oxide nanocrystal growth - Mak, Hong Jun. (2010)
Nano-scale copper oxide play an important role in optoelectronics, photovoltaic, and catalytic applications due to its unique properties. The controlled synthesis of nanoparticles (NPs) has been attributed to the use of capping ligands which binds to NP surface, thus limiting NP size growth and resisting oxidation. In this report, two different experimental methods: polyol reduction and thermal decomposition was employed for the synthesis of Cu/Cu2O/CuO NPs and the surface binding effect of various ligands: oleylamine, oleic acid, trioctylamine, onto the NP surface was investigated using these two methods.